Demographic and socioeconomic characteristics of tuberculosis mortality in San Cristóbal de Las Casas, Chiapas, Mexico 1997-2009 - José Alejandro Meza Palmeros; Héctor Javier Sánchez Pérez; Graciela Freyermuth Enciso; Georgina Sánchez Ramírez (Social Medicine Publication Group, 2014)
Objective: To analyze the demographic and socio-economic characteristics of deceased tuberculosis patients. Subjects: Individuals who died between 1997 and 2009 in San Cristóbal de Las Casas (San Cristóbal), Chiapas, Mexico and had previously been registered as tuberculosis patients. Methods: All reports and death certificates from the San Cristóbal civil registry were reviewed. We identified and analyzed cases in which the cause of death was listed as tuberculosis (n=79). Socio-economic data was taken from the death certificate. To analyze the degree of social marginalization, addresses of decedents were geo-coded by Basic Geostatistical Area (BGA). Results: Most patients dying of tuberculosis had one or more of the following characteristics: 1) they lived in an BGA with high or very high levels of social marginalization, 2) they had low educational attainment; 3) they were peasants, migrants, or housewives, and/or 4) they were not covered by so-cial security. Conclusion: Most patients dying of tuberculosis are socially vulnerable. In order to prevent further mor-tality from tuberculosis in the suburbs of San Cristóbal, TB detection and treatment programs must be significantly strengthened amongst marginalized groups.